Історико-правові аспекти українсько-польської дипломатії у роки Другої світової війни - Гороть, А.; Horot’, А. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розкривають особливості українсько-польської дипломатії в роки Другої світової війни, які характеризуються якісно новим політичним забарвлення і здійснювалися в умовах політичної системи (соціалістичної) та на засадах договірно-правової бази, яка не мала аналогів у попередній багатовіковій історії двох держав. Саме період Другої світової війни найбільш складний у формуванні двосторонньої дипломатії двох сусідніх держав. Тому, що результати Другої світової війни різко змінили ситуацію в українсько- польських відносинах. В даний період політика Польщі щодо українців базувалася на невизнанні їхніх самостійницьких устремлінь та на цілеспрямованій асиміляції, що заохочувалося Москвою. ОУН виступала за налагодження таких взаємин на платформі самостійності двох держав і визнання польською стороною права українців на свої західні етнічні землі.The article deals with the peculiarities of Ukrainian-Polish diplomacy during the Second World War which were characterized by qualitatively new political coloring, were carried out in terms of a new political system (socialist) and on the basis of the legal framework, which had no analogues in the long previous history of both states. It was the period of World War II that appeared to be the most complicated in the shaping of bilateral diplomacy of the two neighboring states, since the Second World War had dramatically changed the situation in the Ukrainian-Polish relations. During this period Poland's policy concerning the Ukrainians was based on the non-recognition of their ambitions of gaining independence and focused on assimilation processes, encouraged and supported by Moscow. OUN advocated establishing bilateral relationships on a platform of independence of the two countries and the recognition by the Polish party the rights of Ukrainians for its western Ukrainian ethnic lands. It has been proved that despite the complexity of Ukrainian-Polish relations during the Second World War, both sides had made attempts to establish mutual understanding between the two nations. The centuries-long history of foreign policy of Ukraine and Poland, like other European nations, has created legacy of diplomatic customs and traditions, the complex of methods and norms that are still of great practical importance in modern trends of state organization.
Historical and Legal Aspects of Ukrainian-Polish Diplomacy During the Second World War.
Keywords: дипломатія; договірно-правова база; двостороннє співробітництво; Організація українських націоналістів; Польща; українсько-польські стосунки; Україна; diplomacy; legal framework; bilateral cooperation; the Ukrainian Nationalists Organization; Poland; Ukrainian-Polish relations; Ukraine